Education and internal migration: Evidence from a child labor reform in Spain - Jorge González Chapela; Sergi Jiménez-Martín; Judit Vall Castelló (SERIEs - Journal of the Spanish Economic Association, 2023)
We exploit a country-wide child labor regulation that eliminated the difference in school/work alternatives for children born at the beginning and the end of the year to identify the causal effect of education on migration at low levels of schooling. By not relying on changes to the school system, we are more confident that our results are not driven by unobserved changes in school quality evolving differentially across regions. The results of a difference-in-differences methodology combined with an exploration of maternal characteristics and a regression discontinuity design suggest that internal migration hardly changed after the reform. A consideration of the external validity of this finding is also provided.
Keywords: I20; J61; R23; 330; Child labor reform; Education; Internal migration; Spain